Keistimewaan Tikrar Al-Qur'an - Alwin Tanjung Tanjung (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2022)
This research examines analytically about tikr?r or repetition of verses in the Koran. This thesis is an answer to some people who do not like the Koran where they think that the repetition of verses contained in the Koran is something that is not systematic. This research uses a type of qualitative research where the data comes from the library (Library Research) which includes primary and secondary data. Then, the discussion in this study is descriptive-analytical in nature, namely by explaining the concept of tikr?r in the Qur'an. The results of this study are: In terms of terminology, it can be concluded that the definition of al-tikrar in the Qur'an is the repetition contained in the Qur'an in the form of recitations, verses, or certain topics such as: stories of the prophets; discussion of heaven and hell; glad tidings and warnings, as well as the repetition of verses or letters, with specific purposes, which is a form of I'jaz al-Qur`an, in terms of style of language and content of meaning. In general, the phenomenon of al-tikrar in the Qur'an is divided into two types, namely repetition of pronunciation and meaning (tikrar al-lafdz wa al-ma'na) and repetition of meaning only, without pronunciation (tikrar al-lafdz duna al- ma'na). The functions of al-tikrar in the Qur'an include li al-taqrir (determination and affirmation) li al-ta`kid (strengthening meaning), li al-ta'zhim (glorifying), li al-tahwil (giving an overview bad and scary).